Indeks Massa Tubuh (IMT) Dan Rasio Lingkar Pinggang Dan Panggul (RLPP) Sebagai Prediktor - Yuriza Agustiningrum; Nur Lathifah Mardiyanti (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Elderly, Hypertension, Body Mass Index, Waist Circumference and Hip. The problem of hypertension is one of the most common diseases in elderly people. Risk factors that can cause hypertension are obesity and central obesity. That is caused by the lack of appropriateness of eating intake with activity in the elderly are declining. So there is a possibility of normal BMI and RLPP will reduce the risk of hypertension. This study aims to determine IMT and RLPP measurements as a predictor of hypertension. This type of research is observational with cross-sectional design and the number of research subjects is 71 elderly who suffer from hypertension and not hypertension. Sampling using total sampling method. Data analysis was done by univariate and bivariate analysis using chi-square test and logistic regression test. The result of statistic test showed that there was a correlation between body mass index with hypertension 0,002 (p <0,002) and BMI was risk factor proved by RR 2,228 (CI 1,3333,723). There is a relationship between RLPP with hypertension 0.000 (p <0.000) and RLPP is hypertension risk factor with RR value 4,340 (CI 1,896-9,933). The result of BMT logistic regression test is not a predictor of hypertension, but RLPP is a predictor to determine hypertension with the formula Y = -3,614 + 2,285X1. It is advisable for the elderly to maintain normal RLPP in order to reduce the risk of hypertension.